2020
DOI: 10.3390/cells9040821
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Mediated Genome Editing Reveals Oosp Family Genes are Dispensable for Female Fertility in Mice

Abstract: There are over 200 genes that are predicted to be solely expressed in the oocyte and ovary, and thousands more that have expression patterns in the female reproductive tract. Unfortunately, many of their physiological functions, such as their roles in oogenesis or fertilization, have yet to be elucidated. Previous knockout (KO) mice studies have proven that many of the genes that were once thought to be essential for fertility are dispensable in vivo. Therefore, it is extremely important to confirm the roles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“… Rohlfs et al (2010) also demonstrated in humans that the zona pellucida (glycoprotein layer surrounding the oocyte) gene ZP3 coevolves with its putative binding partner, ZP3R , in sperm ( Table I ). Furthermore, recent genome editing studies have revealed several other sperm- and oocyte-specific genes that play an important role in gamete interaction ( Abbasi et al , 2020 ; Fujihara et al , 2020 ; Lamas-Toranzo et al , 2020 ; Noda et al , 2020 ). Although the binding partners of these genes remain to be demonstrated in future studies, all of them have a potential to increase our understanding of the molecular mechanisms of gamete incompatibility.…”
Section: Potential (In)compatibility Genes In Humans and Other Mammalsmentioning
confidence: 99%
“… Rohlfs et al (2010) also demonstrated in humans that the zona pellucida (glycoprotein layer surrounding the oocyte) gene ZP3 coevolves with its putative binding partner, ZP3R , in sperm ( Table I ). Furthermore, recent genome editing studies have revealed several other sperm- and oocyte-specific genes that play an important role in gamete interaction ( Abbasi et al , 2020 ; Fujihara et al , 2020 ; Lamas-Toranzo et al , 2020 ; Noda et al , 2020 ). Although the binding partners of these genes remain to be demonstrated in future studies, all of them have a potential to increase our understanding of the molecular mechanisms of gamete incompatibility.…”
Section: Potential (In)compatibility Genes In Humans and Other Mammalsmentioning
confidence: 99%
“…Crispr/Cas9 system was used to reduce the interference of the endogenous GCase activity, as we performed previously ( Abbasi et al, 2020 ). Briefly, HEK293 cells were infected with lentivirus expressing CAS9 protein and sgRNA of GBA1.…”
Section: Methodsmentioning
confidence: 99%
“…In parallel with characterization of genetic mutants, Whole Genome Sequencing (WGS) can be employed to identify the causative mutation. Another approach being undertaken is to use CRISPR-Cas9 to generate knockouts of all testes expressed genes as is being undertaken by several labs to ascertain which knockouts impact fertilization (Miyata et al, 2016;Abbasi et al, 2020). A similar approach could be taken to knock out all oocyte expressed genes.…”
Section: Addressing the Sperm And Egg Gene Discovery Questionmentioning
confidence: 99%